Catalytic electrode and preparation method thereof

By designing the catalytic electrodes of a multi -layer structure, the different pores and pore rates of the first and second sub -layers are used to solve the problem of the traditional catalytic electrodes that cannot take into account the efficiency of electronic conductivity, ion transmission and bubble discharge. Electrochemical reactions.

CN119372689APending Publication Date: 2025-01-28JIANGSU TRINA GREEN HYDROGEN TECHNOLOGY CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411531963.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Traditional single-layer porous catalytic electrodes cannot take into account both electron conductivity, ion transport and bubble discharge efficiency during the hydrogen evolution reaction, resulting in an increase in ohmic resistance, which is not conducive to the operating efficiency of the alkaline electrolytic cell.

Method used

Design a catalytic electrode of a multi -layer structure, including the first subtrashore and the second sub -layer. The pores and pore rates of the first subtracement are small. Poresm catalytic layer.

Benefits of technology

This catalytic electrode can effectively promote electronic transmission, improve the efficiency of ion transmission and bubble discharge in electrolytes, reduce Ohm losses, and improve voltage efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372689A_ABST
    Figure CN119372689A_ABST
Patent Text Reader

Abstract

The invention relates to a catalytic electrode and a preparation method thereof. The catalytic electrode comprises an electrode substrate and a porous catalytic layer, the porous catalytic layer comprises a first sub-layer and a second sub-layer, the first sub-layer is arranged on the electrode substrate, and the second sub-layer is arranged on the side, away from the electrode substrate, of the first sub-layer. The aperture and porosity of the second sub-layer are greater than those of the first sub-layer. The first sub-layer located on the inner layer has a small aperture and porosity, the relatively compact first sub-layer is beneficial to promoting transmission of electrons in the solid-phase catalyst layer, the second sub-layer located on the outer layer has a large aperture and porosity, and the transmission efficiency of ions and bubbles in an electrolyte can be improved through the large aperture and porosity. Therefore, the catalytic electrode can well give consideration to electron conductivity, ion transmission and bubble discharge efficiency, ohmic loss is reduced, and voltage efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrolytic hydrogen production, and in particular to a catalytic electrode and a preparation method thereof. Background Art

[0002] Alkaline electrolyzers are important equipment for large-scale hydrogen production. The electrode performance of alkaline electrolyzers has an important influence on current density and electrolysis efficiency. Catalytic electrodes can act as catalysts for electrochemical reactions, promote the transmission of electrons in the solid-phase catalytic layer, and also play a role in transmitting ions in the electrolyte and gases produced by electrolysis. However, traditional single-layer porous catalytic electrodes are composed of irregular and transverse micropores. During the hydrogen evolution reaction, the electrolyte cannot quickly penetrate into the bottom catalytic layer on the one hand, and as hydrogen is continuously produced, there are no open channels for hydrogen to be quickly discharged, causing the porous structure to be filled with hydrogen, resulting in failure of the porous structure, increasing the ohmic resistance, and being unfavorable for improving the operating efficiency of the alkaline electrolyzer. Summary of the invention

[0003] Based on this, it is necessary to provide a catalytic electrode and a preparation method thereof to solve the problem that traditional catalytic electrodes cannot take into account electronic conductivity, ion transport and bubble discharge efficiency.

[0004] One of the objects of the present invention is to provide a catalytic electrode, the scheme is as follows:

[0005] A catalytic electrode comprises an electrode substrate and a porous catalytic layer, wherein the porous catalytic layer comprises a first sublayer and a second sublayer, wherein the first sublayer is arranged on the electrode substrate, and the second sublayer is arranged on a side of the first sublayer away from the electrode substrate, the pore size of the second sublayer is larger than the pore size of the first sublayer, and the porosity of the second sublayer is larger than the porosity of the first sublayer.

[0006] In one embodiment, the thickness of the first sub-layer is 30 μm-50 μm, and the thickness of the second sub-layer is 30 μm-50 μm.

[0007] In one embodiment, the porosity of the first sub-layer is 5% to 20%, and the porosity of the second sub-layer is 15% to 30%.

[0008] In one embodiment, the material of the electrode substrate includes at least one of nickel and stainless steel.

[0009] In one embodiment, the material of the first sub-layer and / or the second sub-layer includes nickel-molybdenum alloy.

[0010] Another object of the present invention is to provide a method for preparing a catalytic electrode, the scheme is as follows:

[0011] A method for preparing a catalytic electrode comprises the following steps:

[0012] providing an electrode substrate;

[0013] A porous catalytic layer is formed on the electrode substrate, and the porous catalytic layer includes a first sublayer and a second sublayer, the first sublayer is arranged on the electrode substrate, the second sublayer is arranged on a side of the first sublayer away from the electrode substrate, the pore size of the second sublayer is larger than the pore size of the first sublayer, and the porosity of the second sublayer is larger than the porosity of the first sublayer.

[0014] In one embodiment, the step of forming the porous catalytic layer comprises:

[0015] Mixing first raw material particles and first pore-forming particles to obtain a first mixed material, wherein the particle size of the first pore-forming particles is 15 μm to 70 μm;

[0016] Mixing the second raw material particles and the second pore-forming particles to obtain a second mixed material, wherein the particle size of the second pore-forming particles is 15 μm to 90 μm, and the particle size of the second pore-forming particles is larger than that of the first pore-forming particles;

[0017] Applying the first mixed material on the electrode substrate to form a first material layer;

[0018] Applying the second mixed material on the first material layer to form a second material layer;

[0019] The first pore-forming particles and the second pore-forming particles are removed, so that the first material layer forms the first sub-layer, and the second material layer forms the second sub-layer.

[0020] In one embodiment, the material of the first pore-forming particles includes aluminum, and the step of removing the first pore-forming particles includes a first alkali washing treatment.

[0021] In one embodiment, the material of the second pore-forming particles includes aluminum, and the step of removing the second pore-forming particles includes a second alkali washing treatment.

[0022] In one embodiment, the first raw material particles include first nickel powder and first molybdenum powder, and the mass ratio of the first nickel powder, the first molybdenum powder and the first pore-forming particles is 70-80:2-6:20-30.

[0023] In one embodiment, the second raw material particles include second nickel powder and second molybdenum powder, and the mass ratio of the second nickel powder, the second molybdenum powder and the second pore-forming particles is 60-70:2-6:30-40.

[0024] In one embodiment, the process of forming the first material layer and / or the second material layer is a plasma spraying process.

[0025] Compared with the traditional solution, the above catalytic electrode and its preparation method have the following beneficial effects:

[0026] The above-mentioned catalytic electrode and its preparation method are provided with a porous catalytic layer of a multilayer structure on an electrode substrate, and the porous catalytic layer includes a first sublayer and a second sublayer. Among them, the pore size and porosity of the second sublayer are greater than the pore size and porosity of the first sublayer, the first sublayer located in the inner layer has a smaller pore size and porosity, and the relatively dense first sublayer is conducive to promoting the transmission of electrons in the solid-phase catalytic layer, while the pore size and porosity of the second sublayer located in the outer layer are larger, and the larger pore size and porosity can improve the ion transmission and bubble discharge efficiency in the electrolyte. The hydrogen generated in the first sublayer can be quickly discharged from the large pores of the second sublayer, and the electrolyte can also be quickly replenished from the large pores of the second sublayer to the small pores of the first sublayer, so that the above-mentioned catalytic electrode can better take into account the electronic conductivity, ion transmission and bubble discharge efficiency, reduce ohmic loss, and improve voltage efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] FIG1 is a schematic structural diagram of a catalytic electrode according to an embodiment;

[0028] FIG2 is a schematic flow diagram of a method for preparing a catalytic electrode according to an embodiment;

[0029] FIG. 3 is a schematic diagram of a process for forming a porous catalytic layer in a method for preparing a catalytic electrode according to an embodiment.

[0030] Description of reference numerals:

[0031] 100, catalytic electrode; 110, electrode substrate; 120, porous catalytic layer; 121, first sublayer; 122, second sublayer. DETAILED DESCRIPTION

[0032] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are shown in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0033] It should be noted that when an element is referred to as being "disposed on" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.

[0034] In the description of the present invention, it should be understood that the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number or order of the indicated technical features.

[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0036] The present invention provides a catalytic electrode which can be used in hydrogen production by water electrolysis, but is not limited thereto.

[0037] As shown in FIG1 , a catalytic electrode 100 of an embodiment includes an electrode substrate 110 and a porous catalytic layer 120. The porous catalytic layer 120 includes a first sublayer 121 and a second sublayer 122. The first sublayer 121 is disposed on the electrode substrate 110, and the second sublayer 122 is disposed on a side of the first sublayer 121 away from the electrode substrate 110. The pore size of the second sublayer 122 is larger than the pore size of the first sublayer 121, and the porosity of the second sublayer 122 is larger than the porosity of the first sublayer 121.

[0038] The above-mentioned catalytic electrode 100 is provided with a porous catalytic layer 120 of a multilayer structure on the electrode substrate 110, and the porous catalytic layer 120 includes a first sublayer 121 and a second sublayer 122. Among them, the pore size and porosity of the second sublayer 122 are greater than the pore size and porosity of the first sublayer 121, the first sublayer 121 located in the inner layer has a smaller pore size and porosity, and the relatively dense first sublayer 121 is conducive to promoting the transmission of electrons in the solid phase catalytic layer, while the pore size and porosity of the second sublayer 122 located in the outer layer are larger, and the larger pore size and porosity can improve the ion transmission and bubble discharge efficiency in the electrolyte. The hydrogen generated in the first sublayer 121 can be quickly discharged from the large pores of the second sublayer 122, and the electrolyte can also be quickly replenished from the large pores of the second sublayer 122 to the small pores of the first sublayer 121, so that the above-mentioned catalytic electrode 100 can better take into account the electronic conductivity, ion transmission and bubble discharge efficiency, reduce ohmic loss, and improve voltage efficiency.

[0039] In some examples, the material of the electrode substrate 110 includes at least one of nickel and stainless steel. Further, the material of the electrode substrate 110 is nickel.

[0040] In some examples, the electrode substrate 110 is one or more of a nickel mesh, a stainless steel mesh, nickel foam, and nickel felt.

[0041] In some examples, the material of the first sublayer 121 includes a nickel-molybdenum alloy. Further, the material of the first sublayer 121 is a nickel-molybdenum alloy. In some examples, the mass ratio of nickel to molybdenum in the nickel-molybdenum alloy contained in the first sublayer 121 is 70-80:2-6, specifically, for example, 70:2, 70:3, 70:4, 70:5, 70:6, 75:2, 75:3, 75:4, 75:5, 75:6, 80:3, 80:4, 80:5, 80:6, etc.

[0042] In some examples, the pore size of the first sublayer 121 is 15 μm to 70 μm, and the pore size of the second sublayer 122 is 15 μm to 90 μm. The pore sizes of the first sublayer 121 and the second sublayer 122 are set within an appropriate range, the first sublayer 121 located in the inner layer has a smaller pore size, and the relatively dense first sublayer 121 is conducive to promoting the transmission of electrons in the solid-phase catalyst layer, while the second sublayer 122 located in the outer layer has a larger pore size, and the larger pore size can improve the transmission efficiency of ions and bubbles in the electrolyte.

[0043] In some of the examples, the pore size of the first sublayer 121 is 30 μm to 50 μm. Further, in some of the examples, the pore size of the first sublayer 121 is 30 μm to 40 μm. In some of the examples, the pore size of the first sublayer 121 is 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, 32 μm, 34 μm, 36 μm, 38 μm, 40 μm, 42 μm, 44 μm, 46 μm, 48 μm, 50 μm, 52 μm, 54 μm, 56 μm, 58 μm, 60 μm, 62 μm, 64 μm, 66 μm, 68 μm, 70 μm, etc., or a range between any two of the above values.

[0044] In some of the examples, the pore size of the second sublayer 122 is 40 μm to 70 μm. Further, in some of the examples, the pore size of the second sublayer 122 is 50 μm to 70 μm. In some of the examples, the pore size of the second sublayer 122 is 30 μm, 32 μm, 34 μm, 36 μm, 38 μm, 40 μm, 42 μm, 44 μm, 46 μm, 48 μm, 50 μm, 52 μm, 54 μm, 56 μm, 58 μm, 60 μm, 62 μm, 64 μm, 66 μm, 68 μm, 70 μm, 72 μm, 74 μm, 76 μm, 78 μm, 80 μm, etc., or a range between any two of the above values.

[0045] In some examples, the porosity of the first sublayer 121 is 5% to 20%. Further, in some examples, the porosity of the first sublayer 121 is 10% to 15%. In some examples, the porosity of the first sublayer 121 is 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc., or a range between any two of the above values.

[0046] In some examples, the thickness of the first sublayer 121 is 30 μm to 50 μm. In some examples, the thickness of the first sublayer 121 is 30 μm, 32 μm, 34 μm, 36 μm, 38 μm, 40 μm, 42 μm, 44 μm, 46 μm, 48 μm, 50 μm, etc.

[0047] In some examples, the material of the second sublayer 122 includes a nickel-molybdenum alloy. Further, the material of the second sublayer 122 is a nickel-molybdenum alloy. In some examples, the mass ratio of nickel to molybdenum in the nickel-molybdenum alloy contained in the second sublayer 122 is 70-80:2-6, specifically, for example, 70:2, 70:3, 70:4, 70:5, 70:6, 75:2, 75:3, 75:4, 75:5, 75:6, 80:3, 80:4, 80:5, 80:6, etc.

[0048] In some examples, the porosity of the second sublayer 122 is 15% to 30%. Further, in some examples, the porosity of the second sublayer 122 is 20% to 25%. In some examples, the porosity of the second sublayer 122 is 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, etc., or a range between any two of the above values.

[0049] In some examples, the thickness of the second sublayer 122 is 30 μm to 50 μm. In some examples, the thickness of the second sublayer 122 is 30 μm, 32 μm, 34 μm, 36 μm, 38 μm, 40 μm, 42 μm, 44 μm, 46 μm, 48 μm, 50 μm, etc.

[0050] In some examples, the first sublayer 121 is coated on the electrode substrate 110 , and the second sublayer 122 is coated on the first sublayer 121 .

[0051] The present invention provides a method for preparing a catalytic electrode 100 for producing hydrogen by electrolyzing water.

[0052] As shown in FIG. 2 , a method for preparing a catalytic electrode 100 according to an embodiment includes the following steps:

[0053] Step S110 , providing an electrode substrate 110 .

[0054] Step S120, a porous catalytic layer 120 is formed on the electrode substrate 110, and the porous catalytic layer 120 includes a first sublayer 121 and a second sublayer 122. The first sublayer 121 is arranged on the electrode substrate 110, and the second sublayer 122 is arranged on a side of the first sublayer 121 away from the electrode substrate 110. The pore size of the second sublayer 122 is larger than the pore size of the first sublayer 121, and the porosity of the second sublayer 122 is larger than the porosity of the first sublayer 121.

[0055] The preparation method of the above-mentioned catalytic electrode 100 is to set a porous catalytic layer 120 of a multilayer structure on the electrode substrate 110, and the porous catalytic layer 120 includes a first sublayer 121 and a second sublayer 122. Among them, the pore size and porosity of the second sublayer 122 are greater than the pore size and porosity of the first sublayer 121, the first sublayer 121 located in the inner layer has a smaller pore size and porosity, and the relatively dense first sublayer 121 is conducive to promoting the transmission of electrons in the solid phase catalytic layer, while the pore size and porosity of the second sublayer 122 located in the outer layer are larger, and the larger pore size and porosity can improve the ion transmission and bubble discharge efficiency in the electrolyte. The hydrogen generated in the first sublayer 121 can be quickly discharged from the large pores of the second sublayer 122, and the electrolyte can also be quickly replenished from the large pores of the second sublayer 122 to the small pores of the first sublayer 121, so that the above-mentioned catalytic electrode 100 can better take into account the electronic conductivity, ion transmission and bubble discharge efficiency, reduce ohmic loss, and improve voltage efficiency.

[0056] In some examples, in step S110, the material of the electrode substrate 110 includes at least one of nickel and stainless steel. Further, the material of the electrode substrate 110 is nickel.

[0057] In some examples, the electrode substrate 110 is one or more of a nickel mesh, a stainless steel mesh, nickel foam, and nickel felt.

[0058] In some examples, before the step of forming the porous catalytic layer 120 (step S120), the method for preparing the catalytic electrode 100 further includes the following steps:

[0059] The electrode substrate 110 is cleaned to remove contamination on the surface of the electrode substrate 110 .

[0060] The cleaning process, for example, includes placing the electrode substrate 110 in deionized water and ethanol solution in sequence for ultrasonic cleaning.

[0061] The ultrasonic cleaning time is, for example, 5 minutes to 15 minutes, specifically, for example, 10 minutes.

[0062] In some examples, before the step of forming the porous catalytic layer 120 (step S120), the method for preparing the catalytic electrode 100 further includes the following steps:

[0063] The electrode substrate 110 is subjected to an acid wash treatment to wash and remove oxides on the electrode substrate 110 .

[0064] The pickling treatment uses hydrochloric acid, for example. The concentration of the hydrochloric acid is, for example, 0.25 mol / L to 0.35 mol / L, specifically, 0.3 mol / L. The pickling treatment time is, for example, 20 min to 50 min, specifically, 30 min.

[0065] As shown in FIG. 3 , in some examples, the step of forming the porous catalytic layer 120 (step S120 ) includes:

[0066] Step S121: mixing first raw material particles and first pore-forming particles to obtain a first mixed material.

[0067] Step S122, mixing the second raw material particles and the second pore-forming particles to obtain a second mixed material.

[0068] Step S123 , coating the first mixed material on the electrode substrate 110 to form a first material layer.

[0069] Step S124, coating the second mixed material on the first material layer to form a second material layer.

[0070] Step S125 , removing the first pore-forming particles and the second pore-forming particles, so that the first material layer forms a first sub-layer 121 , and the second material layer forms a second sub-layer 122 .

[0071] In some of the examples, the particle size of the first pore-forming particles is 15 μm to 70 μm. Further, in some of the examples, the particle size of the first pore-forming particles is 30 μm to 50 μm.

[0072] In some of the examples, the particle size of the second pore-forming particles is 15 μm to 90 μm. Further, in some of the examples, the particle size of the second pore-forming particles is 50 μm to 80 μm.

[0073] In some examples, in step S121 , the first raw material particles include a first nickel powder and a first molybdenum powder.

[0074] In some of the examples, the mass ratio of the first nickel powder to the first molybdenum powder is 70~80:2~6, for example 70:2, 70:3, 70:4, 70:5, 70:6, 75:2, 75:3, 75:4, 75:5, 75:6, 80:3, 80:4, 80:5, 80:6, etc.

[0075] In some of the examples, the particle size of the first nickel powder is 15 μm to 70 μm. Further, in some of the examples, the particle size of the first nickel powder is 30 μm to 50 μm.

[0076] In some examples, the particle size of the first molybdenum powder is 15 μm to 70 μm. In some examples, the particle size of the first molybdenum powder is 30 μm to 50 μm.

[0077] In some examples, in step S121 , the material of the first pore-forming particles includes aluminum.

[0078] In some of the examples, the mass ratio of the first nickel powder, the first molybdenum powder and the first pore-forming particles is 70-80: 2-6: 20-30. Further, in some of the examples, the mass ratio of the first nickel powder, the first molybdenum powder and the first pore-forming particles is 72-78: 4-6: 22-27. Further, in some of the examples, the mass ratio of the first nickel powder, the first molybdenum powder and the first pore-forming particles is 75: 5: 25.

[0079] In step S125, the step of removing the first pore-forming particles includes a first alkali washing treatment, and the aluminum in the first material layer can be removed by the first alkali washing treatment. Optionally, the alkali solution used in the first alkali washing treatment can be, for example, but not limited to, one or more of a sodium hydroxide solution, a potassium hydroxide solution, etc. In some examples, the concentration of the alkali solution is 25wt%~35wt%, specifically, for example, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, etc. The first alkali washing treatment time is 6h~10h, specifically, for example, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, etc.

[0080] In some examples, in step S122 , the second raw material particles include a second nickel powder and a second molybdenum powder.

[0081] In some of the examples, the mass ratio of the second nickel powder to the second molybdenum powder is 70~80:2~6, for example 70:2, 70:3, 70:4, 70:5, 70:6, 75:2, 75:3, 75:4, 75:5, 75:6, 80:3, 80:4, 80:5, 80:6, etc.

[0082] In some of the examples, the particle size of the second nickel powder is 15 μm to 70 μm. Further, in some of the examples, the particle size of the second nickel powder is 30 μm to 50 μm.

[0083] In some of the examples, the particle size of the second molybdenum powder is 15 μm to 70 μm. Further, in some of the examples, the particle size of the second molybdenum powder is 30 μm to 50 μm.

[0084] In some examples, in step S122 , the material of the second pore-forming particles includes aluminum.

[0085] In some of the examples, the mass ratio of the second nickel powder, the second molybdenum powder, and the second pore-forming particles is 70-80: 2-6: 20-30. Further, in some of the examples, the mass ratio of the second nickel powder, the second molybdenum powder, and the second pore-forming particles is 72-78: 4-6: 22-27. Further, in some of the examples, the mass ratio of the second nickel powder, the second molybdenum powder, and the second pore-forming particles is 75: 5: 25.

[0086] In step S125, the step of removing the second pore-forming particles includes a second alkali washing treatment, and the aluminum in the second material layer can be removed by the second alkali washing treatment. Optionally, the alkali solution used in the second alkali washing treatment can be, for example, but not limited to, one or more of a sodium hydroxide solution, a potassium hydroxide solution, etc. In some examples, the concentration of the alkali solution is 25wt%~35wt%, specifically, for example, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, etc. The second alkali washing treatment time is 6h~10h, specifically, for example, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, etc.

[0087] In some of the examples, in step S124 , the process of forming the first material layer is a plasma spraying process.

[0088] In some of the examples, when forming the first material layer, the power of the plasma spraying process is 40kW~60kW, for example, 40kW, 42kW, 44kW, 46kW, 48kW, 50kW, 52kW, 54kW, 56kW, 58kW, 60kW, etc. The spraying distance is 120mm~150mm, for example, 120mm, 123mm, 126mm, 130mm, 133mm, 136mm, 140mm, 143mm, 146mm, 150mm, etc. The powder feeding speed is 100g / min~130g / min, for example, 100g / min, 103g / min, 106g / min, 110g / min, 113g / min, 116g / min, 120g / min, 123g / min, 126g / min, 130g / min, etc.

[0089] In some of the examples, in step S124 , the process of forming the second material layer is a plasma spraying process.

[0090] In some of the examples, when forming the second material layer, the power of the plasma spraying process is 40kW~60kW, for example, 40kW, 42kW, 44kW, 46kW, 48kW, 50kW, 52kW, 54kW, 56kW, 58kW, 60kW, etc. The spraying distance is 120mm~150mm, for example, 120mm, 123mm, 126mm, 130mm, 133mm, 136mm, 140mm, 143mm, 146mm, 150mm, etc. The powder feeding speed is 100g / min~130g / min, for example, 100g / min, 103g / min, 106g / min, 110g / min, 113g / min, 116g / min, 120g / min, 123g / min, 126g / min, 130g / min, etc.

[0091] The following specific examples are provided to further illustrate the present invention. The present invention provides the following specific examples for a better understanding of the present invention, but is not limited to the specific implementation methods and does not limit the protection scope of the present invention.

[0092] Example 1

[0093] This embodiment provides a catalytic electrode for producing hydrogen by electrolyzing water and a method for preparing the same.

[0094] The method for preparing the catalytic electrode of this embodiment comprises the following steps:

[0095] Step 1: Place the nickel electrode mesh in deionized water and ethanol solution for ultrasonic cleaning in turn, and take it out and dry it after cleaning for 10 minutes.

[0096] Step 2: soak the cleaned nickel electrode mesh in 0.3 mol / L hydrochloric acid for 30 minutes, take it out, rinse it with deionized water, and dry it.

[0097] Step 3, weigh nickel powder with a particle size distribution range of 30-50 μm, molybdenum powder with a particle size distribution range of 30-50 μm, and aluminum powder with a particle size distribution range of 30-50 μm, the mass ratio of nickel powder, molybdenum powder and aluminum powder is 75:5:25, and mix them to obtain a first mixture.

[0098] Step 4, weigh nickel powder with a particle size distribution range of 30-50 μm, molybdenum powder with a particle size distribution range of 30-50 μm, and aluminum powder with a particle size distribution range of 50-80 μm, the mass ratio of nickel powder, molybdenum powder and aluminum powder is 65:5:35, and mix them to obtain a second mixture.

[0099] Step 5, using a plasma spraying process, feeding the first mixed material into a plasma flame flow, spraying it on the nickel electrode mesh to form a first material layer, the plasma spraying power is 45 kW, the spraying distance is 140 mm, and the powder feeding speed is 120 g / min.

[0100] Step 6, using plasma spraying technology, feed the second mixed material into the plasma flame flow, spray it on the first material layer formed in step 5 to form a second material layer, the plasma spraying power is 45kW, the spraying distance is 140mm, and the powder feeding speed is 120g / min.

[0101] Step 7, placing the nickel electrode mesh formed with the first material layer and the second material layer in a KOH solution with a concentration of 30%wt, soaking for 8 hours, removing the aluminum in the first material layer and the second material layer, and obtaining a catalytic electrode for electrolyzing water to produce hydrogen.

[0102] The catalytic electrode prepared in this example was tested for active area using an electrochemical workstation and then placed in an electrolytic cell for testing. The test results are shown in Table 1. The electrochemical active area is 12.19 μF / cm 2 In the electrolytic cell test, when the current density is 4000A / m 2 When , the voltage of the electrolysis chamber is 1.83V.

[0103] Example 2

[0104] This embodiment provides a catalytic electrode for producing hydrogen by electrolyzing water and a method for preparing the same.

[0105] The method for preparing the catalytic electrode of this embodiment comprises the following steps:

[0106] Step 1: Place the nickel electrode mesh in deionized water and ethanol solution for ultrasonic cleaning in turn, and take it out and dry it after cleaning for 10 minutes.

[0107] Step 2: soak the cleaned nickel electrode mesh in 0.3 mol / L hydrochloric acid for 30 minutes, take it out, rinse it with deionized water, and dry it.

[0108] Step 3, weigh nickel powder with a particle size distribution range of 15-30 μm, molybdenum powder with a particle size distribution range of 15-30 μm, and aluminum powder with a particle size distribution range of 15-30 μm, the mass ratio of nickel powder, molybdenum powder and aluminum powder is 75:5:25, and mix them to obtain a first mixture.

[0109] Step 4, weigh nickel powder with a particle size distribution range of 15-30 μm, molybdenum powder with a particle size distribution range of 15-30 μm, and aluminum powder with a particle size distribution range of 30-50 μm, the mass ratio of nickel powder, molybdenum powder and aluminum powder is 65:5:35, and mix them to obtain a second mixture.

[0110] Step 5, using a plasma spraying process, feeding the first mixed material into a plasma flame flow, spraying it on the nickel electrode mesh to form a first material layer, the plasma spraying power is 45 kW, the spraying distance is 140 mm, and the powder feeding speed is 120 g / min.

[0111] Step 6, using plasma spraying technology, feed the second mixed material into the plasma flame flow, spray it on the first material layer formed in step 5 to form a second material layer, the plasma spraying power is 45kW, the spraying distance is 140mm, and the powder feeding speed is 120g / min.

[0112] Step 7, placing the nickel electrode mesh formed with the first material layer and the second material layer in a KOH solution with a concentration of 30%wt, soaking for 8 hours, removing the aluminum in the first material layer and the second material layer, and obtaining a catalytic electrode for electrolyzing water to produce hydrogen.

[0113] The catalytic electrode prepared in this example was tested for active area using an electrochemical workstation and then placed in an electrolytic cell for testing. The test results are shown in Table 1. The electrochemical active area is 10.29 μF / cm 2 In the electrolytic cell test, when the current density is 4000A / m 2 When , the voltage of the electrolysis chamber is 1.86V.

[0114] Example 3

[0115] This embodiment provides a catalytic electrode for producing hydrogen by electrolyzing water and a method for preparing the same.

[0116] The method for preparing the catalytic electrode of this embodiment comprises the following steps:

[0117] Step 1: Place the nickel electrode mesh in deionized water and ethanol solution for ultrasonic cleaning in turn, and take it out and dry it after cleaning for 10 minutes.

[0118] Step 2: soak the cleaned nickel electrode mesh in 0.3 mol / L hydrochloric acid for 30 minutes, take it out, rinse it with deionized water, and dry it.

[0119] Step 3, weigh nickel powder with a particle size distribution range of 30-50 μm, molybdenum powder with a particle size distribution range of 30-50 μm, and aluminum powder with a particle size distribution range of 30-50 μm, the mass ratio of nickel powder, molybdenum powder and aluminum powder is 75:5:25, and mix them to obtain a first mixture.

[0120] Step 4, weigh nickel powder with a particle size distribution range of 30-50 μm, molybdenum powder with a particle size distribution range of 30-50 μm, and aluminum powder with a particle size distribution range of 70-90 μm, the mass ratio of nickel powder, molybdenum powder and aluminum powder is 65:5:35, and mix them to obtain a second mixture.

[0121] Step 5, using a plasma spraying process, feeding the first mixed material into a plasma flame flow, spraying it on the nickel electrode mesh to form a first material layer, the plasma spraying power is 45 kW, the spraying distance is 140 mm, and the powder feeding speed is 120 g / min.

[0122] Step 6, using plasma spraying technology, feed the second mixed material into the plasma flame flow, spray it on the first material layer formed in step 5 to form a second material layer, the plasma spraying power is 45kW, the spraying distance is 140mm, and the powder feeding speed is 120g / min.

[0123] Step 7, placing the nickel electrode mesh formed with the first material layer and the second material layer in a KOH solution with a concentration of 30%wt, soaking for 8 hours, removing the aluminum in the first material layer and the second material layer, and obtaining a catalytic electrode for electrolyzing water to produce hydrogen.

[0124] The catalytic electrode prepared in this example was tested for active area using an electrochemical workstation and then placed in an electrolytic cell for testing. The test results are shown in Table 1. The electrochemical active area is 15.25 μF / cm 2 In the electrolytic cell test, when the current density is 4000A / m 2 When , the voltage of the electrolysis chamber is 1.85V.

[0125] Comparative Example 1

[0126] The preparation method of the catalytic electrode of this comparative example comprises the following steps:

[0127] Step 1: placing the nickel electrode mesh in deionized water and ethanol solution in turn for ultrasonic cleaning.

[0128] Step 2: soak the cleaned nickel electrode mesh in 0.3 mol / L hydrochloric acid for 30 minutes, take it out, rinse it with deionized water, and dry it.

[0129] Step 3, weighing nickel powder with a particle size distribution range of 30-50 μm, molybdenum powder with a particle size distribution range of 30-50 μm, and aluminum powder with a particle size distribution range of 30-50 μm, the mass ratio of nickel powder, molybdenum powder and aluminum powder is 75:5:25, and mixing to obtain a mixture.

[0130] Step 4, using a plasma spraying process, feeding the mixed material into a plasma flame flow, spraying it on the nickel electrode mesh to form a material layer, the plasma spraying power is 45 kW, the spraying distance is 140 mm, and the powder feeding speed is 120 g / min.

[0131] Step 5, placing the nickel electrode mesh with the material layer formed thereon in a KOH solution with a concentration of 30%wt, soaking it for 8 hours, removing the aluminum in the material layer, and obtaining a catalytic electrode for hydrogen production by electrolysis of water.

[0132] The catalytic electrode prepared in this example was tested for active area using an electrochemical workstation and then placed in an electrolytic cell for testing. The test results are shown in Table 1. The electrochemical active area is 5.68 μF / cm 2 In the electrolytic cell test, when the current density is 4000A / m 2 When , the voltage of the electrolysis chamber is 1.95V.

[0133] Compared with Example 1, Comparative Example 1 is a single-layer small pore structure with a smaller electrochemical active area. During the hydrogen evolution reaction, the electrolyte cannot be replenished in time and the liquid inside the pore cannot be quickly removed. Therefore, the ohmic resistance increases and the cell voltage increases significantly.

[0134] Comparative Example 2

[0135] The preparation method of the catalytic electrode of this comparative example comprises the following steps:

[0136] Step 1: placing the nickel electrode mesh in deionized water and ethanol solution in turn for ultrasonic cleaning.

[0137] Step 2: soak the cleaned nickel electrode mesh in 0.3 mol / L hydrochloric acid for 30 minutes, take it out, rinse it with deionized water, and dry it.

[0138] Step 3, weighing nickel powder with a particle size distribution range of 30-50 μm, molybdenum powder with a particle size distribution range of 30-50 μm, and aluminum powder with a particle size distribution range of 50-80 μm, with a mass ratio of nickel powder, molybdenum powder and aluminum powder being 75:5:25, and mixing them to obtain a mixture.

[0139] Step 4, using a plasma spraying process, feeding the mixed material into a plasma flame flow, spraying it on the nickel electrode mesh to form a material layer, the plasma spraying power is 45 kW, the spraying distance is 140 mm, and the powder feeding speed is 120 g / min.

[0140] Step 5, placing the nickel electrode mesh with the material layer formed thereon in a KOH solution with a concentration of 30%wt, soaking it for 8 hours, removing the aluminum in the material layer, and obtaining a catalytic electrode for hydrogen production by electrolysis of water.

[0141] The catalytic electrode prepared in this example was tested for active area using an electrochemical workstation and then placed in an electrolytic cell for testing. The test results are shown in Table 1. The electrochemical active area is 27.67 mF / cm 2 In the electrolytic cell test, when the current density is 4000A / m 2 When , the voltage of the electrolysis chamber is 1.89V.

[0142] Compared with Example 1, Comparative Example 2 is a single-layer macroporous structure with a larger electrochemical active area. The macroporous structure reduces the reaction specific surface area, and during the hydrogen evolution reaction, the structure is prone to collapse under the scouring of a large number of bubbles, resulting in an increase in the cell voltage.

[0143] Comparative Example 3

[0144] The preparation method of the catalytic electrode of this comparative example comprises the following steps:

[0145] Step 1: Place the nickel electrode mesh in deionized water and ethanol solution for ultrasonic cleaning in turn, and take it out and dry it after cleaning for 10 minutes.

[0146] Step 2: soak the cleaned nickel electrode mesh in 0.3 mol / L hydrochloric acid for 30 minutes, take it out, rinse it with deionized water, and dry it.

[0147] Step 3, weigh nickel powder with a particle size distribution range of 30-50 μm, molybdenum powder with a particle size distribution range of 30-50 μm, and aluminum powder with a particle size distribution range of 50-80 μm, the mass ratio of nickel powder, molybdenum powder and aluminum powder is 75:5:25, and mix them to obtain a first mixture.

[0148] Step 4, weigh nickel powder with a particle size distribution range of 30-50 μm, molybdenum powder with a particle size distribution range of 30-50 μm, and aluminum powder with a particle size distribution range of 30-50 μm, the mass ratio of nickel powder, molybdenum powder and aluminum powder is 75:5:25, and mix them to obtain a second mixture.

[0149] Step 5, using a plasma spraying process, feeding the first mixed material into a plasma flame flow, spraying it on the nickel electrode mesh to form a first material layer, the plasma spraying power is 45 kW, the spraying distance is 140 mm, and the powder feeding speed is 120 g / min.

[0150] Step 6, using plasma spraying technology, feed the second mixed material into the plasma flame flow, spray it on the first material layer formed in step 5 to form a second material layer, the plasma spraying power is 45kW, the spraying distance is 140mm, and the powder feeding speed is 120g / min.

[0151] Step 7, placing the nickel electrode mesh formed with the first material layer and the second material layer in a KOH solution with a concentration of 30%wt, soaking for 8 hours, removing the aluminum in the first material layer and the second material layer, and obtaining a catalytic electrode for electrolyzing water to produce hydrogen.

[0152] The catalytic electrode prepared in this example was tested for active area using an electrochemical workstation and then placed in an electrolytic cell for testing. The test results are shown in Table 1. The electrochemical active area is 9.23 mF / cm 2 , in the electrolytic cell test, the electrolytic chamber voltage was 1.91V.

[0153] Compared with Example 1, Comparative Example 3 has a large pore structure at the bottom and a small pore structure at the top. The large pores at the bottom slow down the electron transmission. On the other hand, the large pore structure is easy to collapse under the erosion of bubbles, resulting in the shedding of the coating. At the same time, since there are small pores on the top, the generated gas cannot be quickly removed and is blocked in the pores, resulting in an increase in ohmic resistance and a significant increase in the chamber voltage.

[0154] Table 1

[0155]

[0156] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0157] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A catalytic electrode, characterized in that: It includes an electrode substrate and a porous catalytic layer, wherein the porous catalytic layer includes a first sublayer and a second sublayer, the first sublayer is arranged on the electrode substrate, the second sublayer is arranged on a side of the first sublayer away from the electrode substrate, the pore size of the second sublayer is larger than the pore size of the first sublayer, and the porosity of the second sublayer is larger than the porosity of the first sublayer.

2. The catalytic electrode according to claim 1, characterized in that The thickness of the first sublayer is 30 μm to 50 μm.

3. The catalytic electrode according to claim 1, characterized in that The thickness of the second sublayer is 30 μm to 50 μm.

4. The catalytic electrode according to claim 1, characterized in that The porosity of the first sub-layer is 5% to 20%; and / or the porosity of the second sub-layer is 15% to 30%.

5. The catalytic electrode according to any one of claims 1 to 4, characterized in that The catalytic electrode meets at least one of the following characteristics (1) to (2): (1) The material of the electrode substrate includes at least one of nickel and stainless steel; (2) The material of the first sub-layer and / or the second sub-layer includes nickel-molybdenum alloy.

6. A method for preparing a catalytic electrode, characterized in that: The following steps are involved: providing an electrode substrate; A porous catalytic layer is formed on the electrode substrate, and the porous catalytic layer includes a first sublayer and a second sublayer, the first sublayer is arranged on the electrode substrate, the second sublayer is arranged on a side of the first sublayer away from the electrode substrate, the pore size of the second sublayer is larger than the pore size of the first sublayer, and the porosity of the second sublayer is larger than the porosity of the first sublayer.

7. The preparation method according to claim 6, characterized in that: The steps of forming the porous catalytic layer include: Mixing first raw material particles and first pore-forming particles to obtain a first mixed material, wherein the particle size of the first pore-forming particles is 15 μm to 70 μm; Mixing the second raw material particles and the second pore-forming particles to obtain a second mixed material, wherein the particle size of the second pore-forming particles is 15 μm to 90 μm, and the particle size of the second pore-forming particles is larger than that of the first pore-forming particles; Applying the first mixed material on the electrode substrate to form a first material layer; Applying the second mixed material on the first material layer to form a second material layer; The first pore-forming particles and the second pore-forming particles are removed, so that the first material layer forms the first sub-layer, and the second material layer forms the second sub-layer.

8. The preparation method according to claim 7, characterized in that: The material of the first pore-forming particles includes aluminum, and the step of removing the first pore-forming particles includes a first alkali washing treatment; and / or The material of the second pore-forming particles includes aluminum, and the step of removing the second pore-forming particles includes a second alkali washing treatment.

9. The preparation method according to claim 8, characterized in that: The first raw material particles include first nickel powder and first molybdenum powder, and the mass ratio of the first nickel powder, the first molybdenum powder and the first pore-forming particles is 70-80: 2-6: 20-30; and / or The second raw material particles include second nickel powder and second molybdenum powder, and the mass ratio of the second nickel powder, the second molybdenum powder and the second pore-forming particles is 60-70:2-6:30-40.

10. The preparation method according to any one of claims 7 to 9, characterized in that: The process of forming the first material layer and / or the second material layer is a plasma spraying process.

Citation Information

Cited By

  • Electrode catalyst, catalyst electrode and preparation method thereof

    CN121344644A